Aspectos epidemiológico, clínico e nutricional de crianças e adolescentes com cardiopatia congênita hospitalizadas - SILVA, Valdenise Rodrigues e (2023)
Objective: To evaluate the epidemiological, clinical and nutritional aspects of children and adolescents with congenital heart disease who were hospitalized. Methods: Crosssectional and observational study with children and adolescents with congenital heart disease hospitalized. A form was used referring to patient identification, clinical profile, anthropometric and food consumption. The BioEstat 5.0 program was used. Student's ttest was used with significance level of 5% (p <0.05). Results: Of the 52 patients with heart disease, 53.85% were female. Most 55.77% were classified in the infancy phase. And 100% was Paraense. As to the most prevalent CC type, the VSD was found in 34.62%. Regarding nutritional status, it was found that 44.9% of the evaluated patients had P / I classified as low or very low; 40.38% had lower or very low I / I; 35% presented P / E classified in thinness or accentuated thinness and 30.77% presented BMI / I classified in thinness or accentuated thinness. As for the frequency of meals per day, it was observed that the average lunch and dinner were significantly lower than recommended. And the average afternoon snack and supper were significantly above recommended. Conclusion: It was found that a large proportion of the evaluated patients presented malnutrition and inadequacy regarding the frequency of meals per day, with a worse prognosis for the patient.